UJI MPN JAMU TRADISIONAL KUNIR ASAM YANG DIJUAL DI PASAR CEPOGO, KABUPATEN BOYOLALI - Mustofa, Choiril Hana; Arrosyid, Muchson; Setiawan, Frendi Aviv (CERATA Jurnal Ilmu Farmasi, 2018)
Tamarind herbal medicine is one of the traditional herbal medicine that is still widely consumed by the community. The manufacturing process is still simple and does not pay attention to the cleanliness element does not rule out the possibility of pollution by bacteria, one of which is by Coliform bacteria, this study aims to determine bacterial contamination in acid turmeric herbs which are sold in Cepogo Market, Boyolali Regency. This research is an observational study. Samples were taken by accidental sampling namely turmeric tamarind herbs purchased from 3 sellers of carrying herbs at Cepogo Market. Each sample was examined the MPN value with 2 test steps, namely the presumption test on the Lactose Borth media and the affirmation test on the Brilliant Green Lactose Broth media. Samples tested positive if there are gas bubbles after incubation. The assertion test results are matched with the MPN value table. The results of the study were obtained MPN value of sample A <3 cells / mL, sample B 4 cells / mL, and sample C 3 cells / mL. From the three samples tested, it can be concluded that the sample contained Coliform bacteria contamination. The value produced from the three samples is below the maximum limit of contamination, which is 20 cells / mL and turmeric acid is suitable for consumption